ANTIBIOTIC SUSCEPTIBILITY PATTERN OF ESCHRICHIA COLI ISOLATES FROM CLINICAL SPECIMENS AT PIMS, ISLAMABAD - Khan, Jafar; Khalil, Irum; AbdEl-Salam, Naser M.; Liaqat, Sehrish; Younas, Naila; Mushtaq, Sameerah; Ullah, Riaz (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: E. coli is the most common producer of extended spectrum beta lactamase enzyme (ESBL) which confers broad spectrum resistance to antibiotics like penicillin, cephalosporin and monobactum. Methods and Materials: The present study was carried out at Pakistan Institute of Medical Sciences, Islamabad. The marked resistance was viewed against amoxicilline-clavulanic acid, ceftriaxone and ceftazidime. The most effective drugs established were sulbactum-cefoparazone, amikacin, pepircillin-tazobactum. A total of 220 samples of wide range were selected, i.e., blood, urine, pus, sputum, etc. and were analyzed using various techniques of Gram staining and biochemical identification. Results: After performing antibiotic sensitivity tests, 83% samples came out to be ESBL positive and 17% were ESBL negative. Conclusion: It was concluded that to ensure adequate treatment of infections arising especially from urinary pathogens and controlling spread of bacterial resistant strains, the continuous monitoring by bacterial susceptibility testing is essential.